125Te nuclear magnetic resonance and impedance spectroscopy study of topological insulator Bi2Te3 nanoparticles mixed with insulating Al2O3 nanoparticles. (12th December 2018) - Choi, Dong Min; Lee, Kyu Won; Lee, Cheol Eui
Abstract: We have studied topological insulator Bi2 Te3 nanoparticles mixed with insulating Al2 O3 nanoparticles by means of 125 Te nuclear magnetic resonance (NMR) and impedance spectroscopy. Our 125 Te NMR lineshape measurements revealed the Knight shift of a satellite peak that increased with the mixing ratio of the Al2 O3 nanoparticles, indicating that the mixing increases the surface-to-volume ratio of the Bi2 Te3 nanoparticles. It is also shown that the impedance spectroscopy can be employed as a simple and effective means of distinguishing the surface electrical properties of the topological insulators in general.